2020
DOI: 10.3389/fpsyg.2020.01998
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Suicidal Ideation, and Suicidal Self-Directed Violence Among U.S. Military Personnel and Veterans: A Systematic Review of the Literature From 2010 to 2018

Abstract: Rates of suicide and posttraumatic stress disorder remain high among United States military personnel and veterans. Building upon prior work, we conducted a systematic review of research published from 2010 to 2018 regarding: (1) the prevalence of suicidal ideation, suicide attempt, and suicide among United States military personnel and veterans diagnosed with posttraumatic stress disorder; (2) whether posttraumatic stress disorder was associated with suicidal ideation, suicide attempt, and suicide among Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 99 publications
3
41
1
Order By: Relevance
“…Posttraumatic stress disorder (PTSD), one of the most prevalent and debilitating psychiatric disorders among veterans (Thomas et al., 2010), has been identified as a critical risk factor for suicide, particularly as successful treatment has been shown to reduce suicidal ideation (e.g., Gradus et al., 2013). Prior research has suggested that veterans with PTSD are at an increased risk for suicide relative to veterans without PTSD (see reviews by Holliday et al., 2020; Pompili et al., 2013). Of note, veterans with PTSD have a higher risk of experiencing the full spectrum of suicidal thoughts (e.g., suicidal ideation and suicide planning; Raines et al., 2017), suicide attempts (e.g., Legarreta et al., 2015), and suicide death (Conner et al., 2014).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Posttraumatic stress disorder (PTSD), one of the most prevalent and debilitating psychiatric disorders among veterans (Thomas et al., 2010), has been identified as a critical risk factor for suicide, particularly as successful treatment has been shown to reduce suicidal ideation (e.g., Gradus et al., 2013). Prior research has suggested that veterans with PTSD are at an increased risk for suicide relative to veterans without PTSD (see reviews by Holliday et al., 2020; Pompili et al., 2013). Of note, veterans with PTSD have a higher risk of experiencing the full spectrum of suicidal thoughts (e.g., suicidal ideation and suicide planning; Raines et al., 2017), suicide attempts (e.g., Legarreta et al., 2015), and suicide death (Conner et al., 2014).…”
mentioning
confidence: 99%
“…First, most studies that have examined this association have focused on the link between PTSD diagnostic status and suicide risk. Of the 15 studies included in a review by Holliday and colleagues (2020) that aimed to examine the association between PTSD and suicide attempts, only three studies included measures that provided a continuous score. Although diagnostic status plays an important role in healthcare systems (e.g., treatment planning), the validity of the diagnostic threshold has been criticized as being relatively arbitrary.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While there is extensive research literature on the physical health of wartorn populations worldwide, the psychological effects of war on survivors are not yet well understood (4). Among the most important of these consequences are mood problems and anxiety that have a negative impact on the personal and social life of war survivors (5). Some studies show that the prevalence of depression in all Iranian veterans is 0.71%.…”
Section: Introductionmentioning
confidence: 99%